1997
DOI: 10.1128/jvi.71.3.2550-2554.1997
|View full text |Cite
|
Sign up to set email alerts
|

The herpesvirus saimiri ORF50 gene, encoding a transcriptional activator homologous to the Epstein-Barr virus R protein, is transcribed from two distinct promoters of different temporal phases

Abstract: The mRNA species encoding the herpesvirus saimiri (HVS) homolog of the Epstein-Barr virus R transcriptional activator (termed ORF50) have been identified and used to determine transcriptional start sites within the gene. The first transcript is spliced and starts from a promoter within ORF49 containing a single intron; the second is produced from a promoter within the second exon and is in the same reading frame. The spliced transcript is detected at early times during productive virus replication in OMK cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Reduced CAT activity was observed when the deletion constructs were used to transactivate pAW-CAT2. However, pBK50b was shown to transactivate the ORF 6 promoter to levels similar to those found previously (52). This suggested that the sequences contained within bp 72350 to 72402 of the published sequence, which were deleted in pBK50⌬1, are essential for transactivation by the ORF 50b gene product.…”
Section: Deletion Analysis Of the Carboxy Terminus Of Orf 50supporting
confidence: 77%
See 2 more Smart Citations
“…Reduced CAT activity was observed when the deletion constructs were used to transactivate pAW-CAT2. However, pBK50b was shown to transactivate the ORF 6 promoter to levels similar to those found previously (52). This suggested that the sequences contained within bp 72350 to 72402 of the published sequence, which were deleted in pBK50⌬1, are essential for transactivation by the ORF 50b gene product.…”
Section: Deletion Analysis Of the Carboxy Terminus Of Orf 50supporting
confidence: 77%
“…Gene expression in HVS is modulated by the two major transcriptional regulating genes encoded by open reading frame (ORF) 50 and ORF 57 (41,42,52,54,55). The ORF 57 gene product encodes a multifunctional protein capable of both transactivation and repression of viral gene expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ORF 50 produces two transcripts. The first is spliced containing a single intron and is detected at early times during the productive cycle, whereas the second is expressed later and is produced from a promoter within the second exon (30). In this paper, we show that the ORF 57 gene product represses the transactivation capability of the ORF 50a gene product (which is produced from a spliced transcript), but activates that of ORF 50b (an unspliced transcript).…”
mentioning
confidence: 72%
“…We were particularly interested in determining whether the ORF 57 gene product exerted any regulatory effect on another transcriptional activator encoded by HVS, ORF 50. This gene encodes two transcripts: the first is spliced and is detected at early times during the productive cycle, whereas the second is expressed later and is produced from a promoter within the second exon (30). Therefore, transfection studies were performed to assess the effect of the ORF 57 gene product on the transactivation capability of the ORF 50 gene products.…”
mentioning
confidence: 99%